VLBI measurements for Frequency Transfer - Takiguchi, H; Koyama, Y; Ichikawa, R; Gotoh, T; Ishii, A; Hobiger, T; Hosokawa, M (National Institute of Information and Communications Technology (NICT), 2008)
We compare the frequency transfer precision between VLBI and GPS carrier phase using IVS and IGS observation data in order to confirm the potential of VLBI time and frequency transfer. The results of the VLBI frequency transfer show that the stability follows a 1/tau law very closely. And that shows the stability has reached about 2 x 10-11 at 1 sec. In this study, the results show that VLBI frequency transfer is more stable than GPS on the same baseline and same period. These results show that geodetic VLBI technique has the potential for precise frequency transfer.